Detection of Bartonella spp. in foxes' populations in Piedmont and Aosta Valley (NW Italy) coupling geospatially-based techniques - Viani, Annalisa; Orusa, Tommaso; Divari, Sara; Lovisolo, Stella; Zanet, Stefania; Orusa, Riccardo; Borgogno-Mondino, Enrico; Bollo, Enrico (Frontiers in Veterinary Science, 2025)
Bartonella is a genus of bacteria known to cause various rare but potentially dangerous diseases in humans and wildlife. The objective of this study was to investigate the presence of Bartonella spp. in red foxes (Vulpes vulpes) from Piedmont and Aosta Valley (NW Italy) and to explore the potential association between environmental humidity and Bartonella infection using remote sensing data. A total of 114 spleen samples were collected from hunted red foxes and screened for Bartonella spp. DNA using a qPCR assay targeting the ssrA locus. Samples that tested positive were further analyzed using end-point PCR to detect the ssrA, gltA, and rpoB loci. The overall prevalence of Bartonella spp. infection was found to be 7.9% (9/114), with a prevalence of 6.9% (7/101) in foxes from Piedmont and 15.4% (2/13) in foxes from Aosta Valley. Sequencing results identified Bartonella schoenbuchensis R1 as the most commonly isolated species (5/9, 62.5%), followed by Candidatus “Bartonella gerbillinarum” in two samples (2/9, 28.6%). To investigate the relationship between environmental factors and Bartonella infection, data from NASA USGS Landsat missions (TOA collection) from 2011 to 2022 were processed using Google Earth Engine. The Tasseled Cap Wetness Index (TCW), an indicator of landscape moisture, was calculated for each meteorological season. The study found that Bartonella spp. infections in foxes were positively associated with higher TCW values (>0.7). Canonical Correspondence Analysis further demonstrated a strong link between pathogen prevalence and municipal-level TCW, suggesting that TCW could be used as a parameter to facilitate disease management and control. This study provides a starting point for a more comprehensive epidemiological assessment of Bartonella spp. on a national scale and highlights the potential role of environmental humidity in influencing pathogen distribution.